Allegory, noise, and history: the Arcades Project looks back at the Trauerspielbuch. Issue 4 (2nd October 2019) - Villegas Vélez, Daniel
ABSTRACT: In Convolute N, Benjamin claims that both the Arcades Project and the Trauerspielbuch reject a historiography based on the notion of periods of decline. Reflecting on the sonorous dimension of the dialectical image as presented in Convolute N, I suggest allegory as another link between the two works, which I explore in connection to sound and noise through an example from Monteverdi's Orfeo while remarking on the role of sound in Benjamin.